Women and Politics - Opuene Hart, Akietuwopiribie; Akie Hart LLB, Ere (International Journal on Integrated Education, 2025)
This study investigates the role of women in politics in developed and developing countries, focusing on the challenges and opportunities that have shaped their political engagement over time. It explores the historical context, theoretical underpinnings, and contemporary issues that influence the participation of women in political processes across the globe. The study is anchored in the Gender and Development (GAD) Theory, which emphasizes addressing systemic gender inequalities in political, social, and economic structures. Through a qualitative research approach and content analysis of secondary sources, this study examines how the socio-cultural, economic, and political factors have either facilitated or hindered women's political involvement. The findings reveal that while historical barriers like patriarchal systems and colonialism significantly hindered women's political engagement, contemporary advancements such as women's suffrage movements, feminist advocacies, gender quotas, and increased political activism have provided significant opportunities for women in politics across the globe, with more participation in developed countries. Despite these advancements, the study highlights persistent challenges, including gender-based violence, economic disparities, and cultural norms in developing countries, and family responsibilities, economic disparities in developed countries that limit women’s full participation in governance. The conclusion underscores the transformative impact of women in political institutions, particularly in developed countries like the USA, UK, Germany, France, etc., and developing countries like Rwanda, where women hold a significant portion of legislative seats. The study recommends continued support for gender-inclusive policies, educational programs, and financial resources to empower more women to participate in politics. The study calls for broader structural reforms and cultural shifts to ensure that women can compete on equal footing with men in the political sphere.